Efficacy of arterial spin labeling magnetic resonance imaging with multiple post-labeling delays to predict postoperative cerebral hyperperfusion in carotid endarterectomy. (4th March 2021) - Endo, Hidenori; Fujimura, Miki; Saito, Atsushi; Endo, Toshiki; Ootomo, Kazumasa; Tominaga, Teiji
ABSTRACT: Introduction : Cerebral hyperperfusion (CHP) syndrome is one of the most deleterious complications after carotid endarterectomy (CEA). Arterial spin labeling (ASL) is a promising non-invasive method to evaluate various hemodynamic parameters in cerebrovascular diseases. The aim of this study was to clarify whether ASL with multiple post-labeling delays (PLDs) can predict postoperative CHP after CEA. Methods : Sixty-one patients with carotid artery stenosis treated by CEA were retrospectively analyzed. The asymmetry index of the preoperative CBF was obtained from ASL using 3 PLDs (1525 ms, 2025 ms, and 2525 ms) and single-photon emission computed tomography (SPECT). Cerebrovascular reactivity (CVR) was measured from SPECT with acetazolamide challenge. The slope of the regression line obtained from the asymmetry index of three PLDs was defined as the slope index. Results : The CHP phenomenon was observed in seven patients (11.5%), one of whom developed CHP syndrome (1.6%). Using the CHP phenomenon as a reference standard, the area under the receiver operating characteristics (ROC) was 0.68 for the asymmetry index of the preoperative SPECT, 0.71 for the asymmetry index of the preoperative ASL, 0.73 for CVR, and 0.78 for the slope index. Using the cutoff value obtained by ROC analysis, the slope index demonstrated a sensitivity of 85%, specificity of 74%, positive predictive value of 30% and the negative predictive value of 98% for predicting CHP. Conclusions : The slope index calculated by ASL with multiple PLDs is a useful screening tool to predict postoperative CHP after CEA.